PENAMBAHAN SERBUK LIMBAH KACA DAN ABU DAUN BAMBU TERHADAP KINERJA PAVING BLOCK - Anita Intan Nura Diana; Subaidillah Fansuri (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2021)
Glass is an object that cannot be separated from human life. Based on data from the Minister of Environment and Forestry (LHK) in 2020, it was stated that data on waste in Indonesia reached 67.8 million tons, of which 0.7 million tons were glass waste. It is known that the types of waste produced in Indonesia are organic waste (60%), plastic waste (14%), paper waste (9%), metal (4.3%), glass and wood (12.7%). The purpose of this study was "to know the effect of adding glass waste powder and bamboo leaf ash on the performance of paving blocks". The data needed in this study are primary data and secondary data. The technique used to collect primary data in this research is the experimental method. The data to be analyzed was obtained from the results of testing in the laboratory using 45 samples. Data were analyzed using multiple linear regression test. All analysis using SPSS software which is then presented in the form of tables, pictures and descriptions. The results showed that the average compressive strength of paving blocks was B quality with regression equation Y = 19.010+ (-0.119) X1 + (0.063) X2, while for absorption was D quality with regression equation Y = 10.598+ (-0.094) X1 + (-0.001) X2. In general, the addition of glass waste and bamboo leaf ash has an effect on the compressive strength and water absorption of paving blocks.